LINGUOCULTUROLOGICAL FEATURES IN YESENIN’S LITERATURE - Dilfuza Khudaiberdieva; Andrey Matsyna (Sciental Journals Publishing, 2025)
This article investigates the linguoculturological features present in the literature of Sergei Yesenin, focusing on the intricate interplay between language, culture, and identity. Yesenin’s poetry, deeply rooted in the Russian rural experience, serves as a bridge between linguistic expression and cultural consciousness. By analyzing his poetic imagery, lexical choices, and narrative structures, this study explores how his works encode not only aesthetic beauty but also social values, historical memory, and collective identity. The findings indicate that his poetry functions as a repository of cultural knowledge, reflecting a unique synthesis of natural imagery, folkloric elements, and symbolic representations. The article emphasizes the importance of examining linguistic and cultural dimensions together, as the fusion of these elements offers a more nuanced understanding of literature as a medium for cultural continuity.
Keywords: Sergei Yesenin, linguoculturology, Russian literature, cultural identity, poetic imagery, rural symbolism, lexicon, mental landscape, cultural consciousness, narrative structure